IMPROVING STUDENTS 'ACTIVITIES AND LEARNING RESULTS USING THE USED BOTTLES - Malatua Lumban Gaol (Universitas Negeri Medan, 2019)
This study aims to increase the students’ activity and the learning result in English in learning in the procedure text only reached 61.81. Used bottle is a tool that can be used as an appropriate English learning media to increase the students’ activity and learning result in learning the procedure text. This research method is quantitative that there is the influence of used bottle learning media on student learning Result in procedure text learning. This cycle is carried out in the form of an assessment process that consists of four stages, namely: (1) planning, (2) taking action, (3) observing, and (4) reflecting. This classroom action research was carried out in three cycles. The results of the study presented include the results of tests and non-tests. Student learning result increase the pre-cycle to the first cycle, the first cycle to the second cycle, and the second cycle to the third cycle. The average value before the cycle is 61.81 (low). The average value in the first cycle is 64.31 (medium) or an increase of 2.50, the average value in cycle II is 73.33 (medium) or has an increase of 9.02, and the average value in cycle III is 83.33 (high) or an increase of 10.00.Keywords: activity, used bottles, procedure text, learning result, learning media